2018
DOI: 10.1007/164_2018_148
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Diarylethylamine- and Ketamine-Based New Psychoactive Substances

Abstract: While phencyclidine (PCP) and ketamine remain the most well-studied and widely known dissociative drugs, a number of other agents have appeared since the late 1950s and early 1960s, when the pharmacological potential of this class was first realized. For example, hundreds of compounds have been pursued as part of legitimate research efforts to explore these agents. Some of these found their way out of the research labs and onto illicit markets of the 1960s and following decades as PCP analogs. Other "illicit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 202 publications
0
26
0
Order By: Relevance
“…At the same time, a number of 1,2‐diphenylethylamines, including diphenidine and methoxyphenidine, have attracted attention due to their appearance and classification as new psychoactive substances (NPS) and reports of non‐medical use . A common pharmacological feature shared between many 1,2‐diarylethylamines and related arylcyclohexylamines including phencyclidine (PCP) and ketamine (Figure ) is N ‐methyl‐D‐aspartate (NMDA) receptor blockage and dissociative effects in humans . 1‐[1‐(2‐Fluorophenyl)‐2‐phenylethyl]pyrrolidine (fluorolintane, 2‐FPPP, 2‐F‐DPPy) (Figure ) has appeared as a research chemical and is reported to display dissociative properties in users, although its pharmacological and analytical properties have not yet been extensively characterized.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the same time, a number of 1,2‐diphenylethylamines, including diphenidine and methoxyphenidine, have attracted attention due to their appearance and classification as new psychoactive substances (NPS) and reports of non‐medical use . A common pharmacological feature shared between many 1,2‐diarylethylamines and related arylcyclohexylamines including phencyclidine (PCP) and ketamine (Figure ) is N ‐methyl‐D‐aspartate (NMDA) receptor blockage and dissociative effects in humans . 1‐[1‐(2‐Fluorophenyl)‐2‐phenylethyl]pyrrolidine (fluorolintane, 2‐FPPP, 2‐F‐DPPy) (Figure ) has appeared as a research chemical and is reported to display dissociative properties in users, although its pharmacological and analytical properties have not yet been extensively characterized.…”
Section: Introductionmentioning
confidence: 99%
“…A common pharmacological feature shared between many 1,2‐diarylethylamines and related arylcyclohexylamines including phencyclidine (PCP) and ketamine (Figure ) is N ‐methyl‐D‐aspartate (NMDA) receptor blockage and dissociative effects in humans . 1‐[1‐(2‐Fluorophenyl)‐2‐phenylethyl]pyrrolidine (fluorolintane, 2‐FPPP, 2‐F‐DPPy) (Figure ) has appeared as a research chemical and is reported to display dissociative properties in users, although its pharmacological and analytical properties have not yet been extensively characterized. Fluorolintane is also the fluorinated derivative of 1‐(1,2‐diphenylethyl)pyrrolidine or DPPy, which has been investigated as an NMDA receptor antagonist for possible neuroprotective activities .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ketamine has been studied extensively since the 1960s and its pharmacokinetics is comprehensively described in the literature. 5,7,8,17,[33][34][35][36] The main pathway of the extensive metabolism of ketamine is N-demethylation to norketamine where cytochrome P450 liver enzymes are mainly involved as well as CYP2B6 and CYP3A4, respectively. 17,33,37,38 Furthermore, norketamine is metabolized to hydroxynorketamines (HNKs) and dehydronorketamine (DHNK).…”
Section: Introductionmentioning
confidence: 99%